1993
DOI: 10.1007/bf00400812
|View full text |Cite
|
Sign up to set email alerts
|

Relation of birthweight to maternal plasma glucose and insulin concentrations during normal pregnancy

Abstract: Summary.Maternal diabetes mellitus is complicated by fetal macrosomia and predisposes the offspring to diabetes, but recent evidence indicates that a low, not high, birthweight is associated with a higher incidence of Type 2 (non-insulin dependent) diabetes in adult life. To clarify the relationships between maternal glucose and insulin levels and birthweight, we measured oral glucose tolerance and neonatal weight in a large group (n = 529) of women during the 26th week of pregnancy. Women with gestational dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 21 publications
7
42
3
Order By: Relevance
“…We are uncertain why the results of this study differ from others, but it may reflect the relatively large numbers in our study, the accurate prospectively collected data using a research protocol to measure length, the mode of collection of cord samples, and the use of a specific insulin assay. As predicted, we found correlations with measures of the intrauterine environment such as maternal glycaemia, maternal insulin resistance and maternal BMI, and relationships of these factors with both cord insulin and fetal growth have been reported previously [5][6][7][8][9]. These expected findings provide validation for our insulin results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We are uncertain why the results of this study differ from others, but it may reflect the relatively large numbers in our study, the accurate prospectively collected data using a research protocol to measure length, the mode of collection of cord samples, and the use of a specific insulin assay. As predicted, we found correlations with measures of the intrauterine environment such as maternal glycaemia, maternal insulin resistance and maternal BMI, and relationships of these factors with both cord insulin and fetal growth have been reported previously [5][6][7][8][9]. These expected findings provide validation for our insulin results.…”
Section: Discussionsupporting
confidence: 89%
“…Pedersen [4] proposed that increased fetal growth in diabetic pregnancies is due to increased insulin secretion by the fetus in response to exposure to a high maternal glucose concentration. Birthweight is directly correlated with maternal glycaemia, both fasting and stimulated glucose levels, in the non-diabetic pregnancy [5]. Other environmental factors altering fetal insulin concentrations and growth include maternal insulin sensitivity during pregnancy [6][7][8] and maternal size [9], with associations also seen with maternal nutrition [10], parity [10,11], and social class [10].…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with other studies (15)(16)(17)(18), we demonstrated maternal glycemia within the normal range was correlated with parameters of fetal growth at birth, including weight, length, and BMI. This effect is most pronounced in the mothers in the upper tertile of glycemic values, suggesting the macrosomia seen in pregnancies complicated by type 2, or gestational, diabetes may be a continuum of the effect of "normal" glucose on birth weight in the nondiabetic pregnancy.…”
Section: Multiple Linear Regression Analysissupporting
confidence: 91%
“…Insulin-mediated growth of the fetus reflects maternal glycemia, with birth weight being increased in diabetic pregnancies, and correlates with maternal glycemia, in both fasting and stimulated levels, in the nondiabetic pregnancy (15)(16)(17)(18). The impact of glycemia within the normal range on early postnatal growth in European Caucasians is uncertain.…”
mentioning
confidence: 99%
“…The 20 studies [1,3,4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] that met inclusion criteria provide data on 2,402,643 women. A study from Retnakaran and Shah [4] evaluated the risk for GDM conferred by fetal sex in a first pregnancy and, in those women in whom it was applicable, the analogous risk in a second pregnancy such that, in the pooled analyses, the first and second pregnancies from this study were entered as two separate reports.…”
Section: Resultsmentioning
confidence: 99%